Recombinant tissue plasminogen activator for massive pulmonary thromboembolism - Samejima, Kouki (BMJ Publishing Group, 2013)
Pulmonary thromboembolism (PTE) can result in significant adverse maternal and fetal outcomes. Monteplase—a recombinant tissue plasminogen activator—is considered effective for the treatment of PTE; however, only a few reports have described cases wherein surgical procedures were performed following treatment with monteplase. Here, we present a patient diagnosed with a massive PTE at 28 weeks of gestation leading to maternal cardiac arrest and intrauterine fetal death. The patient was treated with percutaneous cardiopulmonary support and monteplase. Thrombolysis was achieved 30 min after its administration. The patient went into spontaneous labour and delivered a stillborn vaginally. Using gauze tamponade and uterotonic agents, haemostasis was achieved after 4 h, and bleeding completely ceased after 7 h. Thus, we suggest that a thrombolytic agent can be administered in critical cases, even if delivery is expected shortly.